Application of Turbulence Models in the Navier-Stokes Equations Resolution for a Hydraulic Jump Transient Problem - Botari, Alexandre; Arantes, Eudes José (Revista Tecnológica, 2014)
This paper proposes to present an application of CFD programs in a simulation of the flow in a hydraulic jump. Initially, it has been introduced the nonlinear representative equations of the flow and the turbulence models necessary to solve Navier-Stokes equations. Therefore, it will be demonstrated how to resolve theses equations using the numerical methods by means of discretisetion and system solve. Finally, it will be shown a transient problem application in a simulation of a hydraulic jump of horizontal channel. The turbulence model used for proposed problem resolution was the Reynolds Stress Model (RSM), which better represents the physical flow characteristics of the problem. A comparison of the numerical results with experimental data has showed two different behaviors: the free surface in the experimental data presents the level of upstream agreement higher than in the hydraulic jump, therefore, in the first one the experimental data line was immerged in to 90% of volume fraction of water region, by the other hand, in the hydraulic jump, the experimental free surface is in between 70 and 80% of volume fraction of water region.